2014
DOI: 10.3171/2014.6.jns131994
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative high-field MRI for transsphenoidal reoperations of nonfunctioning pituitary adenoma

Abstract: Object. The loss of anatomical landmarks, frequently invasive tumor growth, and tissue changes make transsphenoidal reoperation of nonfunctioning pituitary adenomas (NFAs) challenging. The use of intraoperative MRI (iMRI) may lead to improved results. The goal of this retrospective study was to evaluate the impact of iMRI on transsphenoidal reoperations for NFA.Methods. Between September 2002 and July 2012, 109 patients underwent reoperations in which 111 transsphenoidal procedures were performed and are repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 83 publications
1
22
0
Order By: Relevance
“…Further studies also show reduced operative time and complication rates . Higher rates of gross total resection with image guidance for reoperations has also been described . Tumor type, size, and prior treatments were not accounted for in the current study.…”
Section: Discussionmentioning
confidence: 65%
“…Further studies also show reduced operative time and complication rates . Higher rates of gross total resection with image guidance for reoperations has also been described . Tumor type, size, and prior treatments were not accounted for in the current study.…”
Section: Discussionmentioning
confidence: 65%
“…Studies of the iMRI-assisted treatment of sellar region tumors in adults have shown that the GTR rate for pituitary adenomas improved significantly 3,16 due to the visualization of even small tumor remnants. Intraoperative imaging has also been used for craniopharyngioma surgery, providing good early prediction of total removal and facilitating further resection of remnants.…”
Section: Discussionmentioning
confidence: 99%
“…Intraoperative imaging has also been used for craniopharyngioma surgery, providing good early prediction of total removal and facilitating further resection of remnants. 3 In our pediatric population, we performed 22 craniopharyngioma surgeries in 15 patients. We found that in 5 procedures more than 1 iMRI imaging study was performed, and in 4 of these cases it led to the visualization of tumor remnant and its removal, allowing for complete resection.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes insipidus is the most common complication following pituitary adenoma surgery, and is caused by damage to the pituitary stalk, posterior pituitary, hypothalamus or the blood supply, which results in an insufficient secretion of antidiuretic hormones (26)(27)(28). The results from the present study demonstrated that postoperative complications in the bromocriptine treatment group were more prevalent than those in the group who were not treated with bromocriptine; however, the only post-operative complication that was statistically significant different in prevalence between the two groups was diabetes insipidus.…”
Section: Discussionmentioning
confidence: 99%